2020
DOI: 10.3389/fneur.2020.00059
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender Differences in Emotion Recognition and Theory of Mind After TBI: A Narrative Review and Directions for Future Research

Abstract: A growing body of literature has examined sex differences in a variety of outcomes from moderate-severe traumatic brain injury (TBI), including outcomes for social functioning. Social functioning is an area in which adults with TBI have significant long-term challenges (1-4), and a better understanding of sex and gender differences in this domain may have a significant clinical impact. This paper presents a brief narrative review of current evidence regarding sex differences in one aspect of social functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 85 publications
(95 reference statements)
0
12
1
1
Order By: Relevance
“…However, as is the case for emotion recognition, identified sex differences in social cognition are often small and moderated by other factors (Thompson and Voyer 2014 ) or not present at all (Di Tella et al 2020 ). Although there are studies that do report sex differences (Baron-Cohen et al 2015 ), for ToM, the evidence of sex differences is even more limited (Turkstra et al 2020 ), and an earlier study, using the exact same ToM measure, the MASC test, reported no sex differences for schizophrenia (Fretland et al 2015 ). In spite of this, the public opinion is often that females are better mindreaders than males.…”
Section: Discussionmentioning
confidence: 99%
“…However, as is the case for emotion recognition, identified sex differences in social cognition are often small and moderated by other factors (Thompson and Voyer 2014 ) or not present at all (Di Tella et al 2020 ). Although there are studies that do report sex differences (Baron-Cohen et al 2015 ), for ToM, the evidence of sex differences is even more limited (Turkstra et al 2020 ), and an earlier study, using the exact same ToM measure, the MASC test, reported no sex differences for schizophrenia (Fretland et al 2015 ). In spite of this, the public opinion is often that females are better mindreaders than males.…”
Section: Discussionmentioning
confidence: 99%
“…After compounding all the various emotions that the study sample were asked to analyze into a positive and a negative group, we were able to conclude that the most accurately perceived emotion was “Love”, and the least recognized was “Fear.” “Love” is a complex and, somewhat, problematic emotion, since it can be considered either self-contained or encompassing all other basic emotions. It should also be noted that our group included more women than men, with the former sex potentially situated at an advantage, across the lifespan, in terms of overall “social thinking”, 44 and, especially, when faced with having to recognize a positive affect or display subtleties. 45 This might also be explained by the fact that most of the study participants were married, which is consistent with findings in literature suggesting that a greater intimate-life satisfaction correlates with a greater expertise in recognizing positive, but not negative, emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The fusiform gyrus ( N 5 ) is involved in high-level visual computations undertaken during face perception, object recognition, and reading ( Weiner and Zilles, 2016 ). Worse performance on tasks related to these cognitive functions has been reported after TBI ( Alnawmasi et al, 2019 ; Turkstra et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%